Low-Dose Mitomycin C Decreases the Postoperative Recurrence Rate of Pterygium by Perturbing NLRP3 Inflammatory Signalling Pathway and Suppressing the Expression of Inflammatory Factors - Qie Guo; Xiao Li; Meng-Na Cui; Yu Liang; Xiang-Peng Li; Jun Zhao; Li-Na Wei; Xiao-Lei Zhang; Xiang Hua Quan (Journal of Ophthalmology)
A pterygium is generally believed to be a chronic inflammatory lesion caused by external stimuli that develops from the conjunctiva and grows onto the cornea. Simple bare sclera excision is the most commonly used method to treat pterygium. However, the high postoperative recurrence rate of pterygium remains a persistent challenge. Mitomycin C (MMC) is an antineoplastic antibiotic that inhibits DNA, RNA, and protein synthesis. In recent years, although MMC has proven useful for the treatment of pterygium, its application has been controversial because of its clear toxicity and the possibility of ocular complications. In the current study, we prospectively recruited patients to receive or not receive a local injection of MMC (0.4 mg/ml). Follow-up was conducted with the patients to determine the postoperative recurrence rate of pterygium and/or to observe any ocular complications. The remarkable results demonstrated that MMC can decrease the postoperative recurrence rate of pterygium without leading to serious eye complications. Further results indicated that MMC can inhibit the activation of the NLRP3 inflammatory signalling pathway and thus downregulate the expression of downstream molecules, including IL-18 and IL-1β. MMC also reduced the expression of inflammatory factors TGF-β1, VEGF, and IL-6. In addition to influencing these factors, MMC suppressed neovascularization and the proliferation of corneal fibroblasts to effectively reduce the recurrence rate of pterygium. Taken together, our results provide a theoretical basis for the development of prevention and treatment strategies for pterygium and suggest that MMC is highly effective as an adjunctive treatment after excision of primary pterygia.